Discovery of the first dual G-triplex/G-quadruplex stabilizing compound: a new opportunity in the targeting of G-rich DNA structures? - Amato, Jussara; Pagano, Alessia; Cosconati, Sandro; Amendola, Giorgio; Fotticchia, Iolanda; Iaccarino, Nunzia; Marinello, Jessica; De Magis, Alessio; Capranico, Giovanni; Novellino, Ettore; Pagano, Bruno; Randazzo, Antonio (Biochimica et biophysica acta. General subjects, 2017)
Guanine-rich DNA motifs can form non-canonical structures known as G-quadruplexes, whose role in tumorigenic processes makes them attractive drug-target candidates for cancer therapy. Recent studies revealed that the folding and unfolding pathways of G-quadruplexes proceed through a quite stable intermediate named G-triplex. Virtual screening was employed to identify a small set of putative G-triplex ligands. The G-triplex stabilizing properties of these compounds were analyzed by CD melting assay. DSC, non-denaturing gel electrophoresis, NMR and molecular modeling studies were performed to investigate the interaction between the selected compound 1 and G-rich DNA structures. Cytotoxic activity of 1 was evaluated by MTT cell proliferation assay. The experiments led to the identification of a promising hit that was shown to bind preferentially to G-triplex and parallel-stranded G-quadruplexes over duplex and antiparallel G-quadruplexes. Molecular modeling results suggested a partial end-stacking of 1 to the external G-triad/G-tetrads as a binding mode. Biological assays showed that 1 is endowed with cytotoxic effect on human osteosarcoma cells. A tandem application of virtual screening along with the experimental investigation was employed to discover a G-triplex-targeting ligand. Experiments revealed that the selected compound actually acts as a dual G-triplex/G-quadruplex stabilizer, thus stimulating further studies aimed at its optimization. The discovery of molecules able to bind and stabilize G-triplex structures is highly appealing, but their transient state makes challenging their recognition. These findings suggest that the identification of ligands with dual G-triplex/G-quadruplex stabilizing properties may represent a new route for the design of anticancer agents targeting the G-rich DNA structures. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. [Display omitted] •Identification of the first G-triplex DNA-targeting compound•Results show that the selected compound is a dual G-triplex/G-quadruplex stabilizer.•Compound 1 is endowed with cytotoxic activity on human osteosarcoma cells.